Chloroquine retinal toxicity in Black African patients: comparing visual fields, spectral domain optical coherence tomography (SD-OCT) and fundus autofluorescence (FAF) - Moodley, Ashvira (My University, 2020)
Background: The use of chloroquine is essential and lifesaving in many autoimmune diseases. Unfortunately with long term use, there is an increased risk of developing retinal toxicity. Multiple screening tests are available for recognition of toxicity but limited data on chloroquine retinal toxicity and use of the screening tests are available in South Africa. Objective: To compare visual fields, spectral domain optical coherence tomography (SD-OCT) and fundus autofluorescence (FAF), to determine which of these screening tests best detects chloroquine retinopathy. Method: A prospective, cross-sectional study of 54 patients on chloroquine >3 years. Each patient had a dilated fundus examination, visual fields, SD-OCT and FAF performed. Results: 30-2 visual fields followed by fundus autofluorescence (FAF) showed the highest percentage of abnormal test results in chloroquine patients at 70% and 67% respectively. 30-2 and 10-2 visual fields best correlated with each other when performed in combination, with a percentage agreement of 69% followed by FAF and 10-2 visual fields with a percentage agreement of 61%. SD-OCT yielded few abnormal results (29.6%), with thinning of the outer nuclear layer without ellipsoid zone thinning. Visual field mean deviation (VFMD) was significantly lower in patients with abnormal visual field patterns than normal patients in both 10-2 (p=0.0031) and 30-2 (p<0.0001) visual fields. Conclusion: A combination of tests should be performed when screening for chloroquine retinopathy. Our study revealed that although the 30-2 and 10-2 visual fields best correlated with each other, the 10-2 visual field and FAF yielded the best results when performing different screening tests
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine, 2020